2014
DOI: 10.1002/nbm.3113
|View full text |Cite
|
Sign up to set email alerts
|

Multi-parametric MRI characterization of inflammation in murine skeletal muscle

Abstract: Myopathies often display a common set of complex pathologies that include muscle weakness, inflammation, compromised membrane integrity, fat deposition, and fibrosis. Multi-parametric, quantitative, noninvasive imaging approaches may be able to resolve these individual pathological components. The goal of this study was to use multi-parametric MRI to investigate inflammation as an isolated pathological feature. Proton relaxation, diffusion tensor imaging (DTI), quantitative magnetization transfer (qMT-MRI), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 57 publications
2
54
0
2
Order By: Relevance
“…Активность болезни -достаточно расплывчатое понятие, предпо-лагающее, что изменение сигнала Т2 -результат неспе-цифических процессов, в основе которых лежат такие механизмы, как воспаление, некроз, дистрофия мышц, острая денервация, а также любые обстоятельства, при-водящие к внеклеточному или внутриклеточному отеку, или их комбинации. Этот факт неоднократно был про-демонстрирован у животных и у человека [17][18][19][20]. Физические упражнения умеренной или высокой ин-тенсивности приводят к увеличению сигнала Т2 от мышц в результате накопления воды в миоцитах.…”
Section: активность болезниunclassified
“…Активность болезни -достаточно расплывчатое понятие, предпо-лагающее, что изменение сигнала Т2 -результат неспе-цифических процессов, в основе которых лежат такие механизмы, как воспаление, некроз, дистрофия мышц, острая денервация, а также любые обстоятельства, при-водящие к внеклеточному или внутриклеточному отеку, или их комбинации. Этот факт неоднократно был про-демонстрирован у животных и у человека [17][18][19][20]. Физические упражнения умеренной или высокой ин-тенсивности приводят к увеличению сигнала Т2 от мышц в результате накопления воды в миоцитах.…”
Section: активность болезниunclassified
“…Although it has been suggested that T 2 variations represent a marker of muscle inflammation (33,34), it should be pointed out that a linear relationship of T 2 and intracellular volume has been previously reported (53). On that basis and considering the reduced second and third eigenvalues at day 7, the associated higher T 2 values might actually be related to the expansion of the extracellular component, including, for instance, a widened interstitial space (54,55), rather than to intracellular changes. Overall, the combination and/ or comparison of multimodal MRI with the recently introduced bioluminescence imaging technique (56) would be of interest for monitoring noninvasively and quantitatively the pathophysiological events, such as chronic inflammation, which are associated with skeletal muscle diseases.…”
Section: Discussionmentioning
confidence: 88%
“…Ce terme est intentionnellement vague étant donné qu'une variation de T2 est un processus non spécifique qui peut être engendré par différents mécanismes tels que l'inflammation, la nécrose, la dystrophie musculaire, la dénervation aiguë, ou toute autre situation pouvant être accompagnée par un oedème intracellulaire, extracellulaire, ou mixte. Cela a été montré de façon extensive sur des modèles animaux (Wishnia et al 2001 ;Heemskerk et al 2007 ;Bryant et al 2014 ;Ha et al 2015) ainsi que chez l'homme. L'exercice physique d'intensité modérée a beaucoup augmenté le T2 musculaire par un méca-nisme d'accumulation d'eau dans les myocytes impliqués.…”
Section: « L'activité » De La Maladieunclassified